2014
DOI: 10.1089/dia.2014.0238
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Trial of the Accuracy and Treatment Experience of the Dexcom G4 Sensor (Dexcom G4 System) and Enlite Sensor (Guardian REAL-Time System) Tested Simultaneously in Ambulatory Patients with Type 1 Diabetes

Abstract: The Dexcom G4 sensor was associated with greater overall accuracy than the Enlite sensor during initial (Days 1-3) and later (Days 4-6) use and for glucose levels in the hypoglycemic range. Patients reported a significantly more positive experience using the Dexcom G4 than the Enlite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 20 publications
1
83
0
Order By: Relevance
“…Currently available CGM devices do not measure blood glucose levels <70 mg/dL (3.9 mmol/L) very accurately (112)(113)(114). Nevertheless, CGM can identify many episodes of hypo-and hyperglycemia that would go undetected by BGM (108,115).…”
Section: Pregnancy Complicated By Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently available CGM devices do not measure blood glucose levels <70 mg/dL (3.9 mmol/L) very accurately (112)(113)(114). Nevertheless, CGM can identify many episodes of hypo-and hyperglycemia that would go undetected by BGM (108,115).…”
Section: Pregnancy Complicated By Diabetesmentioning
confidence: 99%
“…Since it is only recently that any devices have even approached such performance, regulatory criteria for device approval have been more pragmatic, focusing on the hazards of incorrect readings (e.g., suboptimal treatment decisions, including improper adjustments in medication dosage, potentially increasing the frequency of both hypoglycemia and hyperglycemia) (58). Accuracy, ergonomics, and ease of use of blood glucose meters have improved dramatically over time (124)(125)(126), and the accuracy of CGM is beginning to approach that of BGM devices (113,114,(127)(128)(129)(130). However, a clinically significant variation in accuracy and precision persists among currently marketed GM devices.…”
Section: Gm Accuracy Precision and Data Display Metricsmentioning
confidence: 99%
“…7 These performance improvements were confirmed in independent assessments. [8][9][10][11] Further improvements were thought needed to meet the stringent requirements of an artificial pancreas system. Accordingly, collaboration between an academic research group from University of Padova and Dexcom resulted in updated noise reduction and a modified calibration algorithm.…”
Section: Original Articlementioning
confidence: 99%
“…The Dexcom G4 sensor used in the current trial has shown higher accuracy in estimating blood glucose levels than other CGM sensors. [31][32][33] High accuracy is likely essential not only for making correct treatment decisions, but also for gaining patients' confidence in using the CGM system. 34 It may also influence the possibility of detecting hypoglycemia, and the Dexcom G4 has shown high accuracy in this glycemic range.…”
Section: Discussionmentioning
confidence: 99%